Phonon Excitation and Energy Redistribution in Phonon Space for Energy Dissipation and Transport in Lattice Structure with Nonlinear Dispersion - Xu, Zhi-Jie (Communications in theoretical physics, 2015)
We first propose fundamental solutions of wave propagation in dispersive chain subject to a localized initial perturbation in the displacement. Analytical solutions are obtained for both second order nonlinear dispersive chain and homogenous harmonic chain using stationary phase approximation. Solution is also compared with numerical results from molecular dynamics （MD） simulations. Locally dominant phonon modes （k-space） are introduced based on these solutions. These locally defined spatially and temporally varying phonon modes k（x, t） are critical to the concept of the local thermodynamic equilibrium （LTE）. Wave propagation accompanying with the nonequilibrium dynamics leads to the excitation of these locally defined phonon modes. It is found that the system energy is gradually redistributed among these excited phonons modes （k-space）. This redistribution process is only possible with nonlinear dispersion and requires a finite amount of time to achieve a steady state distribution. This time scale is dependent on the spatial distribution （or frequency content） of the initial perturbation and the dispersion relation. Sharper and more concentrated perturbation leads to a faster energy redistribution and dissipation. This energy redistribution generates localized phonons with various frequencies that can be important for phonon-phonon interaction and energy dissipation in nonlinear systems. Depending on the initial perturbation and temperature, the time scale associated with this energy distribution can be critical for energy dissipation compared to the Umklapp scattering process. Ballistic type of heat transport along the harmonic chain reveals that at any given position, the lowest mode （k = O） is excited first and gradually expanding to the highest mode （km~（x,t））, where km~（x,t） can only asymptotically approach the maximum mode kB of the first Brillouin zone （kmax（x,t） --~ kB）. NO energy distributed into modes with k_max（x,t） 〈 k 〈 k^B demonstrates that the local thermodynamic equilibrium cannot be established in harmonic chain. Energy is shown to be uniformly distributed in all available phonon modes k ≤ _max（x, t） at any position with heat transfer along the harmonic chain. The energy flux along the chain is shown to be a constant with time and proportional to the sound speed （ballistic transport）. Comparison with the Fourier＇s law leads to a time-dependent thermal conductivity that diverges with time.